Mathematics Education as a Discipline: A Critical Analysis of Metaphysical and Epistemological Foundations - Degu, Yenealem Ayalew (Bahir Dar Journal of Education, 2015)
Mathematics education is situated at the nexus of mathematics and education. As to my information, graduate programs in mathematics education were on and off at Bahir Dar, Haramaya, and Addis Ababa universities over the last ten years. This indicates a reputation problem; the dilemma is whether mathematics education is a field in its own right or not. The objective of this review is, therefore, to critically analyze the metaphysical and epistemological foundations of mathematics education. A mathematics educator’s orientation and awareness about the mathematics teaching, t he aim of mathematics education, the theories of learning process, the students (or environment) and the nature of mathematics are determined by general mathematical and educational philosophies. It is believed that mathematics education has diverging theoretical perspectives. However, there are arguments about whether there is a need to develop own philosophies and theories or adapt from other disciplines. Adapted theories, such as semiotics and mathematical discourse, could be applied. On the other hand, the development of grand philosophy (and theory) of mathematics education could be useful in providing warrants for the field’s autonomy. Theorizing and philosophizing could be opportunities for mathematics education researchers; it is a good opportunity for frontiers to play lots of roles. This review is hoped to bring discussion forum on the issue.